Optimization studies for the removal of nickel from an aqueous solution on to Madhuca Indica leaves powder - K KUMARASWAMY; P.KING; Y PRASANNA KUMAR (International Journal of Pharma and Bio Sciences, 2017)
Industrial evolution, urbanization and agricultural development are highly required for the development of socity and nation. However, untreated or partially treated industrial effluents, sewage waste, domestic waste and agricultural runoffs generate large amounts of pollutants and became major source of water pollution. Wide varieties of organic and inorganic pollutants released into water streams from these sources are highly toxic and pose serious threat to all life forms. Therefore the present work was aimed to evaluate the biosorption potential of madhuca indica leaves for the removal of nickel from aqueous solution. Batch experiments such as contact time, pH of the solution, biosorbent dosage, average partical size of the biosorbent, initial metal concentration and temperature of the aqueous solution were conducted for the removal of nickel from aqueous solution using madhuca indica leaves as biosorbent. The Central Composite Design (CCD) programming was utilized to outline the analyses and to decide the optimum (68% for 25 min contact time) conditions for the present study.